EFEKTIFITAS APLIKASI WEBSITE DALAM PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Ni Rury Heranda Meduri; Rangga Firdaus; Helmy Fitriawan (Akademika : Jurnal Teknologi Pendidikan, 2022)
One of the supporting factors in the success of the teaching and learning process is the use of a learning media. The purpose of this study is to determine the effectiveness of website applications in learning to increase students' interest in learning. Utilization of technology in learning media that will expand student opportunities in efforts to increase learning. Utilization of the website is used and utilized to help students undergo learning, learning that can be done online and offline. The development of ICT is currently experiencing a very rapid increase making it easier for educators and students to find information and data in a practical and effective way. It has also brought a number of very many changes to several aspects of human life which are used to search for and obtain information easily and can be accessed anytime and anywhere. In this study the Systematic Literature Review (SLR) method was used. In collecting data, it was carried out by searching several national journals accredited by Sinta, Google Scholar and Scopus which were then reviewed in these journals in order to obtain conclusions or results from the research that had been carried out. The results of the research carried out are that Website Learning Media can be used in an effort to increase student interest in learning so that it helps students and teachers carry out additional learning outside of school so that learning is not boring and students' interest in learning is high.